EVALUATION OF ETHNOBOTANICAL RESEARCH DEVELOPED IN THE PERUVIAN CONTEXT (2000-2013) - Pizarro, Jose (2020)
The quality of 110 ethnobotanical studies performed in Peru and published during the last thirteen years in peer-reviewed journals was evaluated through an index of research performance, the RPE index. This index assumes a maximum value of one and is composed of ten indicators. The studies with a better performance are valued with scores of the RPE index > 0.5. The indicators were monitors of the expertise on plants of the informants, the experience and specialization of research leaders, the use of participatory techniques during the research, the multidisciplinary character of the research team, the funding support attained, the scientific production, the citation in Google Scholar and the achievement of prior consent from the studied human group. The results show that the studies with scores > 0.51 were performed mainly by foreign scientists, recognized as experienced scientists with training in biological sciences, with a scientific contribution resulting from the ethnobotanical research, and as part of a research team. Furthermore, the studies with best performance were conducted primarily by pharmacologists, scientists from the social sciences and biologists. The studies performed by Peruvian ethnobotanists exhibit lower scores of the RPE index due to factors such as low scientific production and lack of funding support.